ANALISIS PENAWARAN KREDIT PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2010)
A purpose this research to the analysis of influence revenue sharing promotion, third party fund, non-performance finances and market share to credit supply at the industry of Islamic banking in Indonesia. This Study use microeconomic . Can be all data system from statistic monthly of Islamic banking and report Islamic banking of Bank Indonesia Tabulation technique and regression double linear is made the discussion in this research. From analysis result quantitative by using regression indicates that variable of promotion, third party fund, market share has an effect on positive and significant, nonperformance finances variable has an effect on negative and significant. Nevertheless, revenue sharing variable not significant, although has an effect on positive to credit supply at the industry of Islamic banking industry in Indonesia. The suggestion is must existence of continuing research by join model in simultaneous between saving and funding. In other hand policy development of Islamic banking must sharpened and modified in order to market penetration and competitive higher Keywords: Credit Supply, Islamic Banking